Prevalence and characteristics of dengue shock syndrome in an acute care setting - Sarah Mansoor; Aimen Malik; Hammad Akram (Apollo Medicine)
Aims and Objectives: Dengue is a mosquito-borne illness caused by Flaviviridae. Although presents with mild symptoms, occasionally deterioration of circulatory parameters results into dengue hemorrhagic fever (DHF) and/or Dengue shock syndrome (DSS) the later presents with plasma leakage and narrow pulse pressure. The objectives of this study are to quantify and characterize dengue shock syndrome among patients with diagnosed dengue fever at the Holy family hospital in Rawalpindi, Pakistan. Methods: A cross-sectional study was conducted between August 2016 and April 2017. Patients with DF were enrolled, and clinical information was abstracted while following the 2011 World Health Organization classifications and guidelines. Results: In our sample (n = 280), we found a higher proportion was of males (71.1%), <30 years old (~64%) and patients with primary type of infection (~71%). 22.1% suffered from DSS. The average duration of illness among patients was 3.6 days. DSS percentage was higher among patients who were aged <30 years (63%), males (64.5%) had a duration of illness <5 days (82.3%) and suffered from primary infection (60%). The odds of DSS were higher among patients with secondary infection (odds ratio [OR] = 2.0, confidence interval [CI] = 1.12–3.62, P = 0.02) and duration of illness <5 days (OR = 15.58, CI = 7.55–32.13, P < 0.0001) compared to the counterpart groups. Conclusion: The identification of complications of dengue is important in preventing the mortality and morbidity of the disease and reducing the burden on the health-care systems as well as on the community.